The Effect of Small Sided Games Toward Aerobic Capacity (Vo2 Max) Football Player - Oman Hadiana; Didi Muhtarom; Dani Nurdiansyah (JUARA : Jurnal Olahraga, 2019)
Soccer is a game performed for 90 minutes of normal time. In meeting the physical needs of players, it is necessary to maintain and increase aerobic capacity (VO2max). the use of small-sided games in contemporary football is widely used to increase aerobic capacity. The purpose of this study is to examine whether the use of small-sided games can increase the aerobic capacity of soccer players. The method used was an experiment with the randomized pretest-posttest control group design. A total of forty-two soccer players STKIP Muhammadiyah Kuningan Student Activity Unit (UKM) were used as research samples. The retrieval technique used is simple random sampling. The results showed that aerobic capacity significantly increased by 6.62% after being treated in the form of small-sided games.